Cost-effectiveness of safer reproduction strategies to prevent HIV in Zimbabwe. (March 2018) - Hughes, Carolyn Smith; Murombedzi, Caroline; Chirenda, Thandiwe; Chareka, Gift; Mhlanga, Felix; Mateveke, Bismark; Gitome, Serah; Makurumure, Tinei; Matubu, Allen; Mgodi, Nyaradzo; Chirenje, Zvavahera; Kahn, James G; et al.
Abstract: Background: HIV discordance in stable couples is a major driver of new infections, and discordant couples trying to conceive may be particularly at risk. Strategies that can reduce the risk of HIV transmission in these couples include antiretroviral therapy with adequate viral load suppression (ART/VL), oral pre-exposure prophylaxis (PrEP), artificial vaginal insemination (AVI), and semen washing (SW). Understanding the cost-effectiveness of these strategies is important, particularly in HIV endemic settings. Leveraging the ongoing SAFER study in Zimbabwe, we examined the cost-effectiveness of offering these strategies compared to current practice. Methods: The SAFER study is an observational cohort of discordant couples who are trying to conceive. SAFER participants are given a package of safer reproduction services, including counselling and a choice of one or more HIV prevention strategies: ART/VL, PrEP, AVI, or SW. We developed decision models to simulate the use of these strategies and to estimate their cost-effectiveness individually and in combination. Patient uptake of strategies was based on SAFER data. Total net costs and outcomes were assessed over a 30-year horizon from a health system perspective. Costs were derived from SAFER activities using micro-costing, including time and motion observations, and from published literature. Health outcomes were estimated using published literature and were measured in terms of disability-adjusted life-years (DALYs) associated with HIV infection. Incremental cost-effectiveness ratios (ICERs) were calculated using discounted total net health-care costs associated with each safer strategy versus current practice, and discounted DALYs for the seronegative partner and infant. Findings: Providing safer reproduction counselling and a choice of strategies is cost-effective compared with current practice, per the WHO standard of annual gross domestic product (GDP) per capita (US$1008 in Zimbabwe), and remains cost-effective up to 97% ART coverage in the general population. Each individual strategy is more cost-effective than current practice, and each has an ICER less than $875 per DALY averted. Both AVI and ART/VL are cost-saving for couples with an HIV-positive woman, and ART/VL and SW were the most cost-effective strategies for couples with an HIV-positive man. Interpretation: Modelling suggests that offering safer reproduction counselling and services to HIV-discordant couples trying to conceive is likely to be highly cost-effective for HIV prevention. Our findings may inform implementation of these strategies in Zimbabwe, and sub-Saharan Africa. Funding: None.